Moral Homo Islamicus (Islamic Man) Dalam Konteks Ekonomi Islam Modern - Mursal Mursal; Arzam Arzam; Zufriani zufriani; Muhammad Fauzi (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to analyze the assumptions of Islamicus' ideas (theories/concepts) in the context of modern society's behavior which undergoes many changes in preferences which are not adequately described by Homo Economicus which negates morals in conception and makes Self Interest as the goal of maximizing utility. The idea of Homo Islamicus allows it to be collided with modern conditions to find assumptions that are in accordance with the realities that exist in the context of the modern economy. The research uses a literature study (Libarary Research), using Content Analysis as a data analysis tool. This study shows that the idea of Homo Islamicus internalizes the moral and rational portion at a proportional level, oriented to the benefit of the general public which is balanced with the interests of Daruriat Nafsh guided by religious morals. The rational choices made by Homo Islamicus reflect a moral attitude that applies basic axiom values and principles in the form of Tawhid, Equilibrium, Free Will, Respontability, and Justice which makes decisions about the best choices without ignoring existing values. Thus, morality becomes the rail (track) of the rules of the game from rationality in making a choice in the modern Islamic economic arena